2012
DOI: 10.1002/mabi.201200178
|View full text |Cite
|
Sign up to set email alerts
|

Development of Protein‐Cage‐Based Delivery Nanoplatforms by Polyvalently Displaying β‐Cyclodextrins on the Surface of Ferritins Through Copper(I)‐Catalyzed Azide/Alkyne Cycloaddition

Abstract: Protein cages are spherical hollow macromolecules that are attractive platforms for the construction of nanoscale cargo delivery vehicles. Human heavy-chain ferritin (HHFn) is modified genetically to control the number and position of functional groups per cage. 24 β-CDs are conjugated precisely to the modified HHFn in specific locations through thiol-maleimide Michael-type addition followed by copper(I)-catalyzed azide/alkyne cycloaddition (CuAAC). The resulting human ferritins displaying β-CDs (β-CD-C90 HHFn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Eighteen molecules of cyclodextrin were conjugated to the cage using CuAAC reaction. Previous studies using CuAAC reaction method makes use of long linkers such as N-propargyl-3-maleimidopropionamide as an alternative to the propargyl maleimide linker used in this study [32]. Although resulting in slightly enhanced conjugation efficiency, additional reaction steps for synthesis of the long linker can be avoided while maintaining at least 75% conjugation using propargyl maleimide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighteen molecules of cyclodextrin were conjugated to the cage using CuAAC reaction. Previous studies using CuAAC reaction method makes use of long linkers such as N-propargyl-3-maleimidopropionamide as an alternative to the propargyl maleimide linker used in this study [32]. Although resulting in slightly enhanced conjugation efficiency, additional reaction steps for synthesis of the long linker can be avoided while maintaining at least 75% conjugation using propargyl maleimide.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclodextrin was conjugated to the protein cage using copper (I) catalysed azide/alkyne cycloaddtion reaction (CuAAC) following the methods described previously with slight modifications [32]. Cysteine mutations on the cage was reduced by the addition of 15 molar excess of tris(2-carboxyethyl)phosphine (TCEP) and incubated for 1 h at room temperature (RT) on a 3D shaker.…”
Section: Conjugation Of Cyclodextrinmentioning
confidence: 99%
“…Human ferritin has been extensively used as a template for the synthesis of biomimetic nanomaterials and as a protein‐based targeted‐delivery nanoplatform in biomedical research . To display monosaccharides on the surface of human ferritin in a controlled manner, we used previously generated HFPCNs, which have a single cysteine residue (C90) for every subunit on their surface (24 cysteines per cage), as polyvalent nanoplatforms . Previously, we demonstrated that these cysteines are exposed on the surface of the nanoplatforms and are therefore fully available for the attachment of functional moieties …”
Section: Resultsmentioning
confidence: 99%
“…The solution was centrifuged to remove E. coli debris and the supernatant was heated at 60 °C for 10 min, precipitating many of the E. coli proteins, which were removed by centrifugation. The supernatant was loaded onto a 10 mm × 300 mm Superose 6 (GE Healthcare) size exclusion column and eluted with buffer containing 50 m M phosphate, 100 m M NaCl (pH 6.5) at a rate of 0.5 mL min −1 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation